Implementation Of E-Budgeting To Government Performance With Internal Control As A Moderation Variable - Das Prena, Gine; Deviyanti Putri, Putu (E-Jurnal Akuntansi; Vol 30 No 5 (2020), 2020)
This study aims are to examine the effect of implementation of e-budgeting on the government institution performance at the organizational level in the context of local government, this study purposes to find out how the role of internal control moderate the implementing e-budgeting with the government institution performance. Sample for this study is 76 E-budgeting system  user at  BPKAD (Badan Pengelola Keuangan dan Aset Daerah)  and BAPPENDA (Badan Pendapatan Daerah) in Denpasar. anaysis using are Classical Assumption Test, MRA Test (Moderation Regression Analysis), and Partial Test (t-test). The test is carried out using the Statistical Package for Social Science (SPSS) program 25.0. The output of this  1) The implementation of E-budgeting had a significant effect on the performance of local government institution 2) The internal control as a moderating variable could not moderate the implementation of e-budgeting on the government institution performance. Keywords: Implementation E-Budgeting; Government Institution Performance; Internal Control.